1998
DOI: 10.1042/bj3300121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mutations in the transmethylase and dehydrogenase/chelatase domains of sirohaem synthase (CysG) on sirohaem and cobalamin biosynthesis

Abstract: The Escherichia coli CysG protein (sirohaem synthase) catalyses four separate reactions that are required for the transformation of uroporphyrinogen III into sirohaem, initially two S-adenosyl-L-methionine-dependent transmethylations at positions 2 and 7, mediated through the C-terminal, or CysGA, catalytic domain of the protein, and subsequently a ferrochelation and dehydrogenation, mediated through the N-terminal, or CysGB, catalytic domain of the enzyme. This report describes how the deletion of the NAD+-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Moreover, the dehydrogenase activity of CysG was investigated to determine whether it was an essential element for cobalamin biosynthesis by studying the effect of a mutant CysG that had no measurable dehydrogenase activity. Surprisingly, it was found that this mutant worked perfectly in the S. typhimurium CobI pathway, but it did not complement the pathway found in B. megaterium (72). There thus appears to be a subtle difference in the early stages of the S. typhimurium and B. megaterium pathways such that the latter requires an absolute dependency on precorrin-2 dehydrogenase activity.…”
Section: Cobalt Chelationmentioning
confidence: 78%
“…Moreover, the dehydrogenase activity of CysG was investigated to determine whether it was an essential element for cobalamin biosynthesis by studying the effect of a mutant CysG that had no measurable dehydrogenase activity. Surprisingly, it was found that this mutant worked perfectly in the S. typhimurium CobI pathway, but it did not complement the pathway found in B. megaterium (72). There thus appears to be a subtle difference in the early stages of the S. typhimurium and B. megaterium pathways such that the latter requires an absolute dependency on precorrin-2 dehydrogenase activity.…”
Section: Cobalt Chelationmentioning
confidence: 78%
“…Thus the synthesis of sirohaem can be mediated by a single multifunctional enzyme, by the action of two enzymes in tandem or by the concerted efforts of three independent enzymes. While on theoretical grounds, a multifunctional enzyme such as CysG could be argued to directly transfer intermediates from one active site to another, experimental evidence does not suggest that the metabolites are held within the confines of the enzyme [43]. Indeed, the lack of sequence similarity between the dehydrogenase/chelatase domains of CysG, YlnE/F and Met8p suggests that these proteins may have arisen by means of convergent evolution.…”
Section: Review Articlementioning
confidence: 99%
“…In Salmonella the cobA/hemD gene is absent (Raux et al 1996). According to Woodcock et al (1998), it is possible to cluster the available sequences of cobA from a number of bacterial species in three categories: (1) In species such as Bacillus megaterium, P. freudenreichii and P. denitrificans, CobA is a protein of about 25-30 kDa; (2) in E. coli, Salmonella and related bacteria, it is a multifunctional protein of aproximately 50-55 kDa, named CysG, which is composed of a N-terminal domain with precorrin-2 oxidase and ferrochelatase activities involved in transforming precorrin-2 into sirohaem, and a C-terminal domain with S-adenosyl-L-methionine-dependent Uroporphyrinogen III C Methyltransferase (SUMT) activity; and (3) in Paenibacillus macerans, Clostridium josui and Bacillus halodurans, methylase activity is associated to a bifunctional protein (*55 kDa); the transmethylase activity is fused to the uroporphyrinogen III synthase (EC: 4.2.1.75), enzyme responsible of the generation of urogen III from uroporphobilinogen. Based on its size and similarity with other enzymes from the group 3, and the complementation study, the CobA/HemD protein from Lb.…”
Section: Complementation Of a Hemd Mutantmentioning
confidence: 98%